Production Management Analysis of Shuttlecock Cottage Industry Nganjuk Regency Increases Business Revenue from The Perspective of Sharia Management - Asiska Nur Abidah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
One of the most crucial elements of production activities is production management, as without it, none of the activities including home industry, which plays a significant role in the economy will proceed in line with the goals. There is a shuttlecock industry in Nganjuk Regency; this company can be considered a home industry firm that uses production management. On the other hand, supervision inside production management is still lacking. Therefore, the purpose of this research was to describe the management of shuttlecock manufacturing in Nganjuk Regency and to review it using sharia management. This study use qualitative descriptive analysis in case study research. When gathering data using interview, documentation, and observation techniques. The outcomes demonstrated the effectiveness of the production management used in Shuttlecock Nganjuk Regency. Although it is a side gig that provides enough money to cover daily expenses, the shuttlecock industry can contribute to the welfare of these business owners and the community at large by providing additional revenue. However, the organization is not well-structured, and the supervision provided has not operated at its best.